Three Lives of The Saint in Polish Voiceover Translation - Hołobut, Agata (Meta, 2012)
The article adopts a diachronic perspective on Polish screen translation. It compares the voiceover version of the British series The Saint broadcast on public television under the old regime with more recent ones, released twenty-five and thirty years later. The main aim is to analyse traces of socio-cultural manipulation in the consecutive portrayals of the Western reality, with special emphasis on translation practice in the communist era. The first section provides historical background for the research, discussing the role of translated programmes in the first decades of the Polish Television. The second section focuses on manipulative techniques, such as projection, caricature, generalisation and omission, used by the earliest translators of the series to adapt the audiovisual message to the needs of communist propaganda. Specific examples illustrate how the Western reality was distorted to criticise materialism and individualism, promote selfless collectivism and class struggle and shape appropriate civic attitudes. The final section presents a brief overview of symptoms of socio-cultural manipulation in the more recent versions of the series, used to adapt it to the changed socio-political situation in Poland.